The Electability of Women Candidates in The Election of Central Java DPRD in 2014 (Universitas Negeri Semarang, 2015)
The study aims to analyze the factors supporting the electability of women candidates in Central Java DPRD election 2014. This type of research is descriptive. Techniques of data collection used the in-depth interviews with all women members of the Central Java DPRD election results 2014. Data processing techniques are data reduction, data display, concluding and verifying. The study found women candidate’s electability factors because they master/control the political capital, social capital and economics capital. By political capital (party officials) so candidate nominated in small number candidacy and electoral district party base. Social capital (activists of social/professional organizations ) support the loyalty and solidity candidate team and candidate voice, and economics capital to support the political cost. Some of them have kinship with the party elite /social elite so openly their access to social and politics capital. An open list proportional electoral system makes it difficult increasing women representation if not followed party policy affirmations committed. In order to reach the 30% the representation of women in the legislature should be intervention laws forcing the party implementing gender justice policies candidacyPenelitian ini bermaksud menganalisa faktor-faktor pendukung keterpilihan caleg perempuan di DPRD Jawa Tengah dalam Pemilu 2014. Tipe penelitian ini deskriptif.Teknik pengumpulan data menggunakan wawancara mendalam terhadap seluruh perempuan anggota DPRD Jawa Tengah hasil Pemilu 2014. Teknik pengolahan data dalam penelitian ini adalah reduksi data, display data, penarikan kesimpulan dan verifikasi. Hasil Penelitian menemukan faktor-faktor keterpilihan caleg perempuan karena mereka menguasai modal politik (pengurus partai) sehingga dicalonkan dinomor urut kecil dan dapil basis partai, modal sosial (pengurus organisasi sosial/profesi) yang membantu kerja dan mendapat dukungan suara, dan modal ekonomi untuk biaya politik, dan kekerabatan dengan elit partai/sosial membuka akses untuk modal politik dan sosial. Sistem pemilu proprsional terbuka menyulitkan kebijakan afirmasi jika tidak diikuti komitmen partai. Untuk bisa mencapai keterwakilan 30% perempuan di lembaga perwakilan harus ada intervensi undang-undang yang memaksa partai melaksanakan kebijakan berkeadilan gender dalam pencalonan